Early postoperative bone scintigraphy in the evaluation of microvascular bone grafts in head and neck reconstruction - Poissonnet Gilles; Dassonville Olivier; Schuepbach Jonas; Demard Francois (Head & Face Medicine, 2007)
Abstract Background Bone scintigraphy was performed to monitor anastomotic patency and bone viability. Methods In this retrospective study, bone scans were carried out during the first three postoperative days in a series of 60 patients who underwent microvascular bone grafting for reconstruction of the mandible or maxilla. Results In our series, early bone scans detected a compromised vascular supply to the bone with high accuracy (p < 10-6) and a sensitivity that was superior to the sensitivity of clinical monitoring (92% and 75% respectively). Conclusion When performing bone scintigraphy during the first three postoperative days, it not only helps to detect complications with high accuracy, as described in earlier studies, but it is also an additional reliable monitoring tool to decide whether or not microvascular revision surgery should be performed. Bone scans were especially useful in buried free flaps where early postoperative monitoring depended exclusively on scans. According to our experience, we recommend bone scans as soon as possible after surgery and immediately in cases suspicious of vascularized bone graft failure.